Thermodynamic description, diffusivities and atomic mobilities in binary Ni–Os system. (September 2015) - Chen, Juan; Zhang, Cong; Wang, Jiong; Chen, Weimin; Tang, Ying; Zhang, Lijun; Du, Yong
Abstract: A systematical study of thermodynamics and diffusion kinetics in the binary Ni–Os system was performed in the present work by means of CALculation of PHAse Diagram (CALPHAD) method supported by key experiments. Based on all the available experimental phase equilibria, a full thermodynamic assessment of binary Ni−Os system was conducted. A reasonable set of thermodynamic description for the binary Ni−Os system was obtained. Comparisons between the calculated and the measured phase equilibria showed that most of the experimental information can be satisfactorily accounted for by the present thermodynamic description. Moreover, the interdiffusion coefficients in face-centered cubic (fcc) Ni−Os alloys at 1373, 1473, 1523, 1573 and 1623 K were measured by using five groups of Ni−Os semi-infinite diffusion couples together with the Sauer–Freise method. On the basis of the interdiffusion coefficients from the present work and the literature as well as the presently obtained thermodynamic description, atomic mobilities in fcc Ni−Os alloys were then assessed by means of DIffusion-Controlled TRAnsformation (DICTRA) software package. Comprehensive comparisons between the calculated and the measured diffusivities show that most of the experimental data can be well reproduced by the presently obtained atomic mobilities. In addition, the reliability of the atomic mobilities obtained in the present work were further validated by comparing the model-predicted concentration profiles of fcc Ni−Os diffusion couples with the experimental data.